Using alarms as a layer of protection. Issue 1 (12th June 2015) - Stauffer, Todd; Clarke, Peter
Abstract : Alarms and operator response to them are one of the first layers of protection used in preventing a plant upset from escalating to an incident. This article discusses how to evaluate the risk reduction (or the probability of failure on demand) of this layer when it is considered as part of a layer of protection analysis. It examines key factors such as time to respond, operator training, human factors, alarm system performance, and the reliability of the hardware used to annunciate the alarm. Recommendations will be drawn from the ISA‐18.2 standard "Management of Alarm Systems for the Process Industries." Analogy will be drawn with techniques used to analyze safety instrumented functions. © 2015 American Institute of Chemical Engineers Process Saf Prog 35: 76–83, 2016